THE IMAGE OF THE BALKANS IN THE ENGLISH-LANGUAGE PRESS AT THE BEGINNING OF 1990s - Гайдай, Д.Ю. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
For the majority of outside observers the wars on the territory of former Yugoslavia (1991 -1995) were unclear, confusing conflicts between nations, each of which has its own „truth". Commentators tried to explain the roots of bloody conflicts through history of the region, thus emphasizing the uniqueness of Balkan experience. This article analyzes the image of the Balkans in the US and British press in the early stages of the Croatian and Bosnian wars. The study of the media representations of Yugoslav conflicts in 1990s shows the revival in Western states the imperial discourse of the early twentieth century.